A bibliometric analysis of insurance literacy using bibliometrix an R package - Shamsuddin, Siti Nurasyikin; Ismail, Noriszura; Roslan, Nur Firyal (AIP conference proceedings, 2022)
Recently, literacy on insurance topics has steadily grown and has gain greater interest among researchers, as shown by the recent increase in publications with an annual growth rate of 8.6%. This study examines the research background of insurance literacy by conducting a comprehensive bibliometric analysis of the insurance literacy topic throughout time, focusing on research trends and the evolution of research interests in this subject. The Scopus database was used as the basis for this research, with the Bibliometrix R package (Biblioshiny) as a software tool with the search query "literacy", "knowledge", "proficiency", "understand" and "insurance". A total of 386 documents was retrieved and analysed, and the results showed an increased growth rate of literature on insurance lapse from 1953 until 2020. Thus, this article contributes to the field by explicitly providing a detailed overview of the scientific output in insurance literacy and its evolution worldwide. These findings can act as a reference point for future researchers in insurance literacy studies.